1998
DOI: 10.1099/0022-1317-79-10-2313
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a new whitefly-transmissible bipartite geminivirus infecting tomato in Panama.

Abstract: Tomato yields from fields and greenhouses are often reduced due to virus infection. In a number of cases, geminiviruses have been identified as the disease-causing agents. Geminiviruses are small plant viruses with circular single-stranded DNA (ssDNA) genomes encapsidated in twinned (geminate) particles (Harrison, 1985). Members have been divided into three subgroups on the basis of their genome organization and host range (Murphy et al., 1995). Members of the genus Begomovirus (previously known as subgroup II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
26
0
5
Order By: Relevance
“…, Tomato yellow mosaic virus (ToYMV) was described as an occasional pathogen of potato (S. tuberosum) in the state of Aragua, Venezuela. Unfortunately, ToYMV is the most important neotropical begomovirus of tomatoes in the Caribbean Basin, where it affects tomato production in Guadeloupe, Martinique, Trinidad and Tobago, Puerto Rico and the Dominican Republic in the Antilles Urbino et al 2004), Panama (Engel et al 1998), Colombia (Morales 2006a), Venezuela (Nava et al 2006), and other Latin American regions considered part of the Caribbean Basin. Unfortunately, ToYMV is the most important neotropical begomovirus of tomatoes in the Caribbean Basin, where it affects tomato production in Guadeloupe, Martinique, Trinidad and Tobago, Puerto Rico and the Dominican Republic in the Antilles Urbino et al 2004), Panama (Engel et al 1998), Colombia (Morales 2006a), Venezuela (Nava et al 2006), and other Latin American regions considered part of the Caribbean Basin.…”
Section: South Americamentioning
confidence: 99%
See 1 more Smart Citation
“…, Tomato yellow mosaic virus (ToYMV) was described as an occasional pathogen of potato (S. tuberosum) in the state of Aragua, Venezuela. Unfortunately, ToYMV is the most important neotropical begomovirus of tomatoes in the Caribbean Basin, where it affects tomato production in Guadeloupe, Martinique, Trinidad and Tobago, Puerto Rico and the Dominican Republic in the Antilles Urbino et al 2004), Panama (Engel et al 1998), Colombia (Morales 2006a), Venezuela (Nava et al 2006), and other Latin American regions considered part of the Caribbean Basin. Unfortunately, ToYMV is the most important neotropical begomovirus of tomatoes in the Caribbean Basin, where it affects tomato production in Guadeloupe, Martinique, Trinidad and Tobago, Puerto Rico and the Dominican Republic in the Antilles Urbino et al 2004), Panama (Engel et al 1998), Colombia (Morales 2006a), Venezuela (Nava et al 2006), and other Latin American regions considered part of the Caribbean Basin.…”
Section: South Americamentioning
confidence: 99%
“…The first begomovirus affecting tomato production in this region was described in 1998 (Engel et al 1998) as Tomato leaf curl virus, but was later recognized as a strain of ToYMV. The first begomovirus affecting tomato production in this region was described in 1998 (Engel et al 1998) as Tomato leaf curl virus, but was later recognized as a strain of ToYMV.…”
Section: Central Americamentioning
confidence: 99%
“…), Potato yellow mosaic Panama virus (PYMPV) (Engel et al. ; Valderrama et al. ), Tomato golden mottle virus (ToGMoV) (Maxwell et al.…”
Section: Introductionmentioning
confidence: 99%
“…BLAST analysis of two PCR products' sequences of the distinct viruses (GenBank Accession Nos. KP313717 for PYMPV and KP318651 for ToLCSiV, respectively) revealed that KP313717 shared 99 % DNA sequence identity with PYMPV -[Panama:Divisa:Tomato:1996] (PYMPV-[PA:Div:Tom:96], (Y15034) (Engel et al, 1998), and KP318651 99 % identity with ToLCSiV -[Nicaragua:Santa Lucia] (ToLCSiV-[NI:SL], (AJ608286) (Rojas et al, 2005) and three other ToLCSiV sequences: [Nicaragua:Santa Lucia] (AJ508779), [Nicaragua:Sebaco] (AJ508780) (Rojas et al, 2005), and [Costa Rica:Alajuela] (AF131213); as well as 98 % identity with ToLCSiV-[Nicaragua:Condega] (AJ508778) (Rojas et al, 2005).…”
Section: This Analysis Revealed Potato Yellow Mosaic Panama Virus (Pymentioning
confidence: 99%
“…This corresponds to an incidence of 26% (8 plants) in open field, and 43% (41 plants) in greenhouse crops. Primers specific for ten tomato-infecting begomoviruses found in Central America (Engel et al, 1998;Nakhla et al, 2005; Table 1) were used to typify the PCR-positive samples.…”
Section: Figurementioning
confidence: 99%